The Linguistic Nature of Neologisms and Their Development in the Context of Globalization - Buronova, Ra’no Abdujabborovna (The Lingua Spectrum, 2026)
This article provides a comprehensive and systematic analysis of the phenomenon of neologisms, which occupy an important place in modern linguistics. It examines the factors contributing to their emergence, their linguistic nature, formation mechanisms, and principles of classification. In addition, the methods of naming neologisms, their narrow and broad interpretations, as well as their semantic and functional features are consistently explored. The article also reviews the main scientific approaches to the study of neologisms – namely stylistic, denotative, lexicographic, concrete-historical, structural, dynamic, psycholinguistic, cognitive, linguocultural, and sociolinguistic perspectives – and analyzes their distinctive features on a scientific basis. It is shown that each of these approaches sheds light on the formation and development of neologisms from different viewpoints, while also possessing certain advantages and limitations. Furthermore, the article highlights the role of neologisms in the context of globalization, revealing their close connection with social development, science, and technological progress. In particular, the rapid development of information technologies, the Internet, and mass communication has significantly contributed to the swift formation and widespread dissemination of new lexical units. The research findings confirm that neologisms play a crucial role in enriching and renewing the lexical system of a language, as well as adapting it to modern communicative needs. Moreover, their functional significance in language development, practical applications, and prospects for further theoretical study are substantiated, leading to the formulation of general scientific conclusions.